DIDACTIC COMMUNICATIONS IN SCOPE OF INFORMATION TECHNOLOGIES AS A CONSISTENT HABIT PATTERN - NEUPOKOEVA, E.; CHAPAEV, N.; AKIMOVA, O.; CHUBARKOVA, E.; TOKAR, A. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The goal of this study is to reveal the problems preparing vocational education teachers for interpersonal interactions in the IT scope, which are solved by teaching consistent habits of didactic communications in this sphere. In addition, at the same time, to show that the formation of consistent habits of didactic communications should be realized entirely and systematically. Observation, interrogation, testing, measuring, and comparing performance results were methods applied in the process of the empiric part of the study. In addition, there are questions related to the formation of consistent habits of didactic communications in the IT sphere. RESUMEN El objetivo de este estudio es revelar los problemas que preparan a los maestros de educación vocacional para las interacciones interpersonales en el ámbito de las IT, que se resuelven enseñando hábitos consistentes de comunicaciones didácticas en esta esfera. Además, al mismo tiempo, para mostrar que la formación de hábitos consistentes de comunicaciones didácticas debe realizarse de manera completa y sistemática. La observación, el interrogatorio, las pruebas, la medición y la comparación de los resultados de desempeño fueron métodos aplicados en el proceso de la parte empírica del estudio. Además, hay preguntas relacionadas con la formación de hábitos consistentes de comunicaciones didácticas en la esfera de IT.